In-plane adaptive retrieval control for a noncooperative target by tethered space robots. (27th September 2016) - Meng, Zhongjie; Wang, Bingheng; Huang, Panfeng; Liu, Zhengxiong
Using tether to replace rigid arms, the tethered space robot has more flexibility and security than the traditional space robot, which gives it a wide application prospect in the satellite retrieval. After a noncooperative satellite is captured by the tethered space robot, the tethered space robot and the satellite compose a combination with uncertain mass, inertia, and tether junction position. The tether length, tether deflection, and combination attitude are coupled seriously and control inputs are strictly limited, which make the retrieval of tethered space robot very difficult. First, a retrieval dynamic model of in-plane motion is derived using Lagrangian method. Then, in order to solve the uncertainty problems of dynamics parameters, an adaptive controller and its parameter updating law are proposed using the dynamic inversion theory. Moreover, an anti-windup strategy with auxiliary variables is derived to compensate the limited control inputs. Simulation results validate the feasibility of the proposed adaptive anti-windup control method. The noncooperative satellite is retrieved along the desired trajectory effectively.